2012
DOI: 10.1016/j.jfma.2011.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Association between human IL-10 gene polymorphisms and serum IL-10 level in patients with food allergy

Abstract: The two SNPs at -1082A/G and -592A/C of IL-10 were associated with FA in our Taiwanese population, and FA patients with the genotype AA/AA haplotype homozygotes had lower serum IL-10 levels. This suggests that IL-10 might play a critical role in the pathogenesis of FA. We suggest that it may be practicable to evaluate the serum IL-10 levels of FA patients and to predict the possibility of FA if genotypes and haplotypes are checked regularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
15
3
1
Order By: Relevance
“…The IL-10 SNP rs3024496 is shown to be related to inflammatory response with increased levels of IgE to dust mite[38], or decreased production of IL-10 by peripheral blood leukocytes[39], and with prostate[40] and colorectal[41] cancer, but has not been shown to be associated with IBD. The IL-10 rs1800872 is associated with IBD[37] and also with increased serum IL-10 levels in CD[42,43], as well as with irritable bowel syndrome[44] and cancer susceptibility[42,43,45,46]. In this study, we found that IL-10 rs3024496 is associated with pediatric IBD, and rs1800872, although by itself is not associated with pediatric IBD, appears to contribute to pediatric IBD via epistatic interaction with rs3024496.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-10 SNP rs3024496 is shown to be related to inflammatory response with increased levels of IgE to dust mite[38], or decreased production of IL-10 by peripheral blood leukocytes[39], and with prostate[40] and colorectal[41] cancer, but has not been shown to be associated with IBD. The IL-10 rs1800872 is associated with IBD[37] and also with increased serum IL-10 levels in CD[42,43], as well as with irritable bowel syndrome[44] and cancer susceptibility[42,43,45,46]. In this study, we found that IL-10 rs3024496 is associated with pediatric IBD, and rs1800872, although by itself is not associated with pediatric IBD, appears to contribute to pediatric IBD via epistatic interaction with rs3024496.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, multiple genes and their variants have been interrogated for their association with FA. Since FA, like AD, was primarily thought to be a disease of the immune system, all of the genes investigated and found to be associated with FA, aside from FLG , were immune-related and included the major histocompatibility complex cluster, CD14, FOXP3, STAT6, SPINK5, TNF, GSTP1, IL13, IL10 , 111113 and IL4RA . 114 In general, these were small-scale, candidate-gene studies that lacked replication, and the findings were frequently inconsistent among studies.…”
Section: Gene-environment Interactions In Atopic Disordersmentioning
confidence: 99%
“…Our previous work also found that IL-10-producing B cells were less in the intestine of mice with food allergy [19, 20]. Clinical study indicates that IL-10 gene polymorphism is associated with food allergy and lower serum IL-10 levels [21]. Others also found that the myeloid-derived monocytes express IL-10, which suppresses most immune effector cells [22].…”
Section: Discussionmentioning
confidence: 88%